2022
DOI: 10.1080/0886022x.2022.2079528
|View full text |Cite
|
Sign up to set email alerts
|

Pro- and anti-fibrotic effects of vascular endothelial growth factor in chronic kidney diseases

Abstract: Renal fibrosis is the inevitable common end-point of all progressive chronic kidney diseases. The underlying mechanisms of renal fibrosis are complex, and currently there is no effective therapy against renal fibrosis. Renal microvascular rarefaction contributes to the progression of renal fibrosis; however, an imbalance between proangiogenic and antiangiogenic factors leads to the loss of renal microvasculature. Vascular endothelial growth factor (VEGF) is the most important pro-angiogenic factor. Recent stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…Regarding TH , which is involved in tyrosine-to-dopamine conversion, there are no results regarding its involvement in kidney fibrosis. Finally, VEGFA , a growth factor essential for both physiological and pathological angiogenesis, can inhibit the expression of Smad3 and miR192, thereby suppressing TGF-β-induced EMT and improving renal fibrosis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding TH , which is involved in tyrosine-to-dopamine conversion, there are no results regarding its involvement in kidney fibrosis. Finally, VEGFA , a growth factor essential for both physiological and pathological angiogenesis, can inhibit the expression of Smad3 and miR192, thereby suppressing TGF-β-induced EMT and improving renal fibrosis [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Based on the difference in the α-subunits, HIFs are divided into three subtypes: HIF-1, HIF-2, and HIF-3. Reportedly, oxidative factors induced renal fibrosis by regulating the expression and activity of HIF-1 via PHD, ERK, and PI-3 K/AKT pathways [ 57 , 58 ]. Therefore, the MAPK, Ras, PI3K-Akt, FoxO, and HIF-1 signaling pathways are closely related to the occurrence and development of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is also of importance for maintaining renal microcirculation and tubular cell vitality. In this respect, VEGF could be nephroprotective [109]. However, some studies showed the opposite [110].…”
Section: Nephroprotectionmentioning
confidence: 97%